2009
DOI: 10.1007/s10886-009-9603-y
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of Gramine by the Cereal Aphid Sitobion avenae

Abstract: Secondary metabolites play an important role in host plant resistance to insects, and insects, in turn, may develop mechanisms to counter plant resistance mechanisms. In this study, we investigated the toxicity of gramine to the cereal aphid Sitobion avenae and some enzymatic responses of S. avenae to this alkaloid. When S. avenae fed on an artificial diet containing gramine, mortality occurred in a dose-dependent manner. The LC 50 of gramine was determined to be 1.248 mM. In response to gramine, S. avenae dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…Plant secondary metabolites such as phenolics, terpenoids and nitrogen-containing metabolites are generally involved in plant defense against insect attacks [17], [31], [32], and adversely affect the feeding behavior and survival of insects [27], [33]. Gramine is a simple alkaloid that exists in some terrestrial gramineous crops and confers defense against aphids [14], [29], [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant secondary metabolites such as phenolics, terpenoids and nitrogen-containing metabolites are generally involved in plant defense against insect attacks [17], [31], [32], and adversely affect the feeding behavior and survival of insects [27], [33]. Gramine is a simple alkaloid that exists in some terrestrial gramineous crops and confers defense against aphids [14], [29], [34].…”
Section: Discussionmentioning
confidence: 99%
“…They are also regarded as a resource for the discovery of novel biological insecticides [13]. Gramine is a simple indole alkaloid found only in some terrestrial gramineous crops ( Triticeae crops) [14], and has been reported to be a deterrent and/or toxicant to some herbivorous insects such as aphids ( Rhopalosiphum padi and Sitobion avenae ) and cotton bollworm ( Helicoverpa armigera ) [15][17]. However, little is known whether gramine is synthesized by hydrophytic plants such as rice, or whether this compound has the ability to confer resistance to attacks by BPHs.…”
Section: Introductionmentioning
confidence: 99%
“…Insects use a variety of amines as neurotransmitters and neuromodulators 3639 . Plants also generate a variety of amines that may play a role in resistance to insect herbivores 4042 . For these reasons, we screened a panel of biogenic and trace amines for agonist and antagonist activity at insect Orco subunits.…”
Section: Introductionmentioning
confidence: 99%
“…In the tobacco cutworm, Spodoptera litura , sublethal doses of the widely occurring plant glycoside rutin resulted in a significant increase in midgut carboxylesterase activity [13]. It was also found that COEs can be induced by indole alkaloid gramine in Sitobion avenae , and the increase of COE activity was positively correlated with dietary gramine concentrations, suggesting that COEs were involved in gramine detoxification [14]. In addition, quercetin, rutin and 2-tridaconone can also induce the activities of COEs in insects [15,16].…”
Section: Introductionmentioning
confidence: 99%